An effect of simplifying magic rules for answering recursive queries in deductive databases - Mamat, Ali; Mat Deris, Mustafa (Faculty of Computer Science and Information Technology, University of Malaya, 1997)
The basic magic sets transformation algorithm for rewriting logical rules in deductive databases is very clear and straightforward. However, rules generated by the algorithm for answering queries are too many compared to the original rules. Therefore, it is useful to simplify the generated rules before they are evaluated. This paper reports the study on the effect of simplifying such rules from the aspect of computing time. It is concluded that the improvement as a result of simplification is quite significant.